2022
DOI: 10.5114/hm.2023.115860
|View full text |Cite
|
Sign up to set email alerts
|

State of mood, motivation, and impulsivity of young athletes: a cross-sectional study

Abstract: Purpose. the aim of the study was to compare the mood, motivation, and impulsivity of young athletes of different sexes and ages. Methods. the sample consisted of 147 young student-athletes of both sexes, aged 12-17 years, participating in the regional stage of the Brazilian Youth School Games 2018. the individuals were categorized into 4 groups for analysis considering sex (male vs. female) and age ( 14 years and 15 years). Results. (1) Female athletes aged 14 years demonstrated greater instability of mood co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Considering the results of these studies, the HIIT intervention induced higher negative changes in mood profiles compared to the MICT. In addition to these supporting findings, the physical tiredness after a training session induced increased adverse feelings, such as anxiety, anger, and depression [42,43]. Furthermore, in a similar study, the results of RPE scores demonstrated a negative correlation with psychological responses, regardless of the participants' physical activity levels [40].…”
Section: Discussionmentioning
confidence: 82%
“…Considering the results of these studies, the HIIT intervention induced higher negative changes in mood profiles compared to the MICT. In addition to these supporting findings, the physical tiredness after a training session induced increased adverse feelings, such as anxiety, anger, and depression [42,43]. Furthermore, in a similar study, the results of RPE scores demonstrated a negative correlation with psychological responses, regardless of the participants' physical activity levels [40].…”
Section: Discussionmentioning
confidence: 82%
“…In cadet category, the results of the analysis of the effect of service quality on achievement motivation were not as large as the junior and senior categories. However, the potential for increasing achievement motivation tends to be greater in the cadet category because athletes at the age of 15 -16 years old still have enthusiasm in practicing (Prieto et al, 2023;Costa et al, 2023). In addition, athletes have not been bored because the average training experience is still less than three years.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review corroborates that Profile of Mood States (PoMS) predicts athletic perfor-mance consistently [3], in line with a robust body of knowledge [3][4][5][6]. PoMS has also been considered a tool to support training demands management and facilitate physical and mental recuperation [7,8]. Moreover, PoMS has been used to avoid management overtraining, impulsivity, burnout, risk of staleness [1,8], and pathogenic behaviours in athletes (e.g., eating disorders and muscle dysmorphia) [9].…”
Section: Introductionmentioning
confidence: 88%
“…PoMS has also been considered a tool to support training demands management and facilitate physical and mental recuperation [7,8]. Moreover, PoMS has been used to avoid management overtraining, impulsivity, burnout, risk of staleness [1,8], and pathogenic behaviours in athletes (e.g., eating disorders and muscle dysmorphia) [9].…”
Section: Introductionmentioning
confidence: 99%